2020
DOI: 10.1002/jdd.12478
|View full text |Cite
|
Sign up to set email alerts
|

Social media as a learning tool: Dental students’ perspectives

Abstract: Objectives This study explored the perceptions of dental students in Saudi Arabia for implementing social media as an educational tool. Methods A cross‐sectional survey was conducted among dental students in 3 governmental dental schools in the western region of Saudi Arabia. A validated questionnaire was used to explore social media use and student perceptions on the advantages and disadvantages of implementing social media in dental education. Descriptive statistics and Pearson's’ χ2, Kruskal‐Wallis, and Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
3
23
1
4
Order By: Relevance
“…This theme indicated that DSM platforms provide various means that genuinely encourage users to allocate considerable time, ranging from connecting with friends to browsing the latest news and exploring other posts, making it time-consuming. These findings are supported by a previous study among dental students who believed that using DSM was time-consuming and distracted them from their studies [27].…”
Section: Discussionsupporting
confidence: 84%
“…This theme indicated that DSM platforms provide various means that genuinely encourage users to allocate considerable time, ranging from connecting with friends to browsing the latest news and exploring other posts, making it time-consuming. These findings are supported by a previous study among dental students who believed that using DSM was time-consuming and distracted them from their studies [27].…”
Section: Discussionsupporting
confidence: 84%
“…This was statistically significant compared to Finnish students who used more hours on Jodel for the assignments or tutorials. This contrasts with a study from Saudi where dental students preferred to use Facebook for their learning [21].…”
Section: Discussioncontrasting
confidence: 64%
“…This is not surprising but reflects the current habits of communication among young adults. Recent studies from different fields of study have reported that undergraduate students spent on average about three to four hours per day using social media platforms [18][19][20][21]. These services include mainly entertainment and communication, but also learning and searching for general information.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of the learning effect would certainly improve the competitiveness of students. Several studies have confirmed that the use of social media promoted development of effective work relationships and were helpful for a successful professional career [32,33]. Inspired by the clinical cases delivered by teachers through social media, students gained knowledge of the impact of restorative procedures on mucosa, periodontal tissues, occlusion, and oral function.…”
Section: Cbl Extended Traditional Teachingmentioning
confidence: 96%